GUIDED INQUIRY LEARNING USING PHET SIMULATIONS BASED WORKSHEET TO IMPROVE STUDENTS’ CONCEPTUAL UNDERSTANDING ON KINETIC THEORY OF GASSES - HIDAYAH, NURUL; , DWIKORANTO (Inovasi Pendidikan Fisika, 2018)
The purpose of this study is to describe the improvement of students? concept understanding after the guided inquiry learning using PhET Simulations based worksheet. This type of research is pre-experimental with One Group Pretest-Posttest design. The subject of the research is the XI Science 1 and XI Science 2 Class of Al Falah Islamic School in Surabaya. This research only use experimental class without comparison class (control) to find out the results of the research do not happen by accident. The normality and homogenity test showed that the sample used in this research are from the normal and homogenous population. The improvement of students conceptual understanding is analyzed by using paired t-test and normalized gain test. The paired t test results indicate that there is a difference in the results of students? improvement after the learning. The improvement of students conceptual understanding improved pretty well with the score of 0,60 for XI Science 1 and the score of 0,65 for XI Science 2.The improvement also occurs for all indicators of understanding i.e. Interpreting, Comparing, Classifying, Summarizing, Exemplifying, Explaining, and Inferring. Based on the results of the research, it can be concluded that the guided inquiry learning using PhET Simulations based worksheet is able to improve the concept understanding of students.